HEALTH STATUS OF THE AGED POPULATION: AN OVERVIEW OF INDIAN LITERATURE - HARIHARAN, Dr. R. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
This paper reviews the health status of aged population in India. Aged Persons will be one of the major policy concerns of the twenty-first century. Health care of the aged is a major concern of a society as old people are more prone to morbidity than young age groups. Most primary surveys have reported that the aged in developed countries in general and the aged population in India in particular have serious health problems. The review analysed health status of the aged persons based on their various short and long term morbidities, psychological problems, social problems, activities of daily living, low intake of nutritional food, family background and financial dependence of the aged persons in India. Around 6 per cent of the aged in India are immobile due to various disabling conditions. Approximately 50 per cent of the elderly suffer from chronic diseases. Visual and hearing impairments are highly prevalent. At the same time, the availability of health services for the elderly was lacking. Knowledge among health workers on the specific needs of the elderly is also minimal. Little attention is paid to the enormous needs of the elderly population. However, this trend clearly reveals that health status of aged persons will be a very big issue to the future society and vast resources need to be directed towards the support and health care of the aged population. Thus, the present paper suggests the researchers to bring various researches in the field of aged population for improving their health status